What Are the Gospels? Richard Burridge’s Impact on Scholarly Understanding of the Genre of the Gospels - Walton, Steve (Currents in biblical research, 2015)
A quiet revolution has taken place in the scholarly understanding of the Gospel genre since the publication of Richard Burridge’s What Are the Gospels? in 1992, reversing the earlier consensus that the canonical Gospels should not be considered biographies. Burridge’s research has been widely accepted and has produced a new consensus, that the Gospels are a species of ancient biography (βίος). This article: (i) lays out the former consensus and demonstrates its widespread acceptance; (ii) outlines the key arguments of Burridge’s research and the contribution he made; (iii) provides evidence of the shift in the scholarly consensus to Burridge’s view that the Gospels are ancient biographies; (iv) maps discussion of genre in recent Gospel commentaries; and (v) suggests further work that is opened up by the new consensus, notably in fine-tuning the identification of the Gospel genre.